Problem wewnętrznej niespójności norm prawnych motu proprio Traditionis custodes co do celebransa i korzystania z tradycyjnych ksiąg liturgicznych w świetle kanonów 17, 18, 20 KPK z 1983 r. - Mielnik, Dawid (Łódzkie Studia Teologiczne, 2025)
The purpose of this article is to attempt to show and explain the reason for the inconsistency of the legal norms of Traditionis custodes regarding the person of the celebrant and the use of traditional liturgical books. The problem is addressed on the basis of canons 17, 18 and 20 of the Code of Canon Law of John Paul II. The analyses were divided into two parts. First, the topic of consent for the celebration of the traditional Mass was analysed, then – the problem of the scope of the use of traditional liturgical books. On the basis of the analyses, it should be concluded that the reason for the problems described in the work is the lack of a clear take on the rules to be applied to a specific group of priests and probably the legislator’s lack of precise knowledge of what rules govern the traditional Roman liturgy.